1994
DOI: 10.1159/000284869
|View full text |Cite
|
Sign up to set email alerts
|

Delusional Misidentification in Alzheimer’s Disease: A Summary of Clinical and Biological Aspects

Abstract: Delusional misidentification symptoms (DMS) are common in Alzheimer’s disease (AD) and they are frequent sources of serious distress for patients and particularly caregivers. We observed DMS in around 30% of the patients with moderate to severe AD in two independent prospective studies; the Capgras type, phantom boarder, mirror and TV DMS were found most frequently. Patients with DMS showed increased EEG delta-power over the right hemisphere, their CT scans showed more severe right frontal lobe atrophy, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 6 publications
1
56
1
4
Order By: Relevance
“…Subsequent analysis by the same group has demonstrated that impairment in verbal fluency and visuospatial function is restricted to the misidentification/ hallucination subtype, that the paranoid subtype does not differ from nonpsychotic AD patients on cognitive measures, and the ability to detect meaningful biologic associations of AD+P would be enhanced by separate analyses of the misidentification and paranoid delusional phenotypes [11]. These results were consistent with the study of Forstl and colleagues [12] that found that delusions of misidentification were associated with greater cognitive impairment than the absence of delusions in a sample of patients with moderate to severe AD.…”
Section: Phenomenologysupporting
confidence: 81%
“…Subsequent analysis by the same group has demonstrated that impairment in verbal fluency and visuospatial function is restricted to the misidentification/ hallucination subtype, that the paranoid subtype does not differ from nonpsychotic AD patients on cognitive measures, and the ability to detect meaningful biologic associations of AD+P would be enhanced by separate analyses of the misidentification and paranoid delusional phenotypes [11]. These results were consistent with the study of Forstl and colleagues [12] that found that delusions of misidentification were associated with greater cognitive impairment than the absence of delusions in a sample of patients with moderate to severe AD.…”
Section: Phenomenologysupporting
confidence: 81%
“…It is possible that partial volume effects-as a result of greater atrophy in the striatum of patients without delusions-might have contributed to the observed differences. Although data suggest that there may be structural differences between patients with and without psychosis in relation to cortical atrophy-right frontal 34 and temporal 35 regions have been specifically implicated-there are no such data relating to the striatum.…”
Section: Results Descriptive and Neuropsychological Testmentioning
confidence: 98%
“…The age at onset was between 65 and 70 years or 85 years and older. To avoid bias in evaluating symptoms due to the progression of the disease, the enrollees were limited to patients with AD at the mild and moderate stages (within 6 years from the onset and a Mini-Mental State Examination (MMSE) 8 score of [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The exclusion criteria were as follows: probable AD with an age at onset between 71 and 84 years (n = 94); an MMSE score below 10 (n = 50); possible AD (n = 22) according to NINCDS-ADRDA criteria; vascular dementia (n = 68); dementia with Lewy bodies (n = 17); frontotemporal dementia (n = 10); alcoholic dementia (n = 4); other types of dementia (n = 79); ageassociated cognitive decline 9 (n = 20); delirium (n = 4); delusional disorder (n = 20); mood disorder (n = 32); and a history of psychotropic drug use (n = 96).…”
Section: Methodsmentioning
confidence: 99%
“…Most previous AD studies indicate that normal aging is accompanied by a decrease in perfusion in the frontal lobe. [17][18][19] Taking age-related changes in the frontal lobe into account, in previous studies patients with DMS exhibited an increased electroencephalography delta-power in the right hemisphere 20 and a significant hypometabolism in the paralimbic and left medial temporal areas. 21 In contrast, patients with hallucinations demonstrate diminished regional cerebral blood flow in the right parietal and left medial temporal lobes 22 and hypoperfusion in the parietal lobe.…”
Section: Characteristics Of Bpsd In Untreated Oldest Old Ad Patientsmentioning
confidence: 99%